Psychological protection and approaches to psychotherapeutic correction of patients with chronic ischemia of a brain at an initial stage - I. V. Hyanikyaynen; V. A. Mikhailov; A. V. Smirnov; T. V. Andrianova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In order to identify the psychosocial characteristics of patients with chronic cerebral ischemia there were examined 280 patients of the organized population of Petrozavodsk (the median age 53,9±8,1 years; gender index 1:1). The control group consisted of persons (n=32) without signs of cerebrovascular disease, similar to the group of patients by sex and age composition (p>0,05). It is established that for persons with a debut of a cerebrovascular disease the increase of the general indicator of tension of mechanisms of psychological protection due to «denial», «compensations», «projections», «regressions», «replacement», «jet education» is typical. Identified psychosocial predictors of patients with chronic cerebral ischemia should be considered when organizing the provision of psychotherapeutic care.